IMPLEMENTASI PERENCANAAN KAS SEBAGAI UPAYA UNTUK MENCIPTAKAN REALISASI ANGGARAN YANG PROPORSIONAL PADA KANTOR BADAN KEUANGAN DAN ASET DAERAH KABUPATEN KUTAI BARAT - Ida Rahmawati, Yeremia Bernat, Elfreda Aplonia Lau (EKONOMIA, 2018)
The purpose of this study was to determine and analyze the implementation of cash planning conducted by the Office of the Regional Finance and Asset Agency of West Kutai Regency and the realization of a proportional budget. The formulation of this research problem is